2017
DOI: 10.1186/s12974-016-0783-4
|View full text |Cite
|
Sign up to set email alerts
|

WWL70 attenuates PGE2 production derived from 2-arachidonoylglycerol in microglia by ABHD6-independent mechanism

Abstract: Backgroundα/β-Hydrolase domain 6 (ABHD6) is one of the major enzymes for endocannabinoid 2-arachidonoylglycerol (2-AG) hydrolysis in microglia cells. Our recent studies have shown that a selective ABHD6 inhibitor WWL70 has anti-inflammatory and neuroprotective effects in animal models of traumatic brain injury and multiple sclerosis. However, the role of ABHD6 in the neuroinflammatory response and the mechanisms by which WWL70 suppresses inflammation has not yet been elucidated in reactive microglia.MethodsThe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 37 publications
1
16
1
1
Order By: Relevance
“…Finally, we also investigated the effect of WWL70 on PGE 2 levels. Indeed, recent studies suggested that the antiinflammatory effects of WWL70 were partially due to an inhibition of mPGES1 and thus an attenuation of PGE 2 production (34). Surprisingly, in our hands, WWL70 administration increased PGE 2 levels in the lungs.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…Finally, we also investigated the effect of WWL70 on PGE 2 levels. Indeed, recent studies suggested that the antiinflammatory effects of WWL70 were partially due to an inhibition of mPGES1 and thus an attenuation of PGE 2 production (34). Surprisingly, in our hands, WWL70 administration increased PGE 2 levels in the lungs.…”
Section: Discussioncontrasting
confidence: 74%
“…Besides the substrates of ABHD6, we thought to quantify PGE 2 in the lungs of mice treated with WWL70. Indeed, a recent study suggested ABHD6-independent effects for WWL70 via the inhibition of mPGES 1 and 2 (mPGES1/2) and thus decreased production of PGE 2 (34). Because in the LPS-treated animal the antiinflammatory effects of WWL70 would have masked a potential direct effect of WWL70 on mPGES1/2, we decided to assess whether administration of WWL70 (20 mg/kg, i.p.)…”
Section: Effect Of Wwl70 On the Substrates Of Abhd6 In Lungs And Alvementioning
confidence: 99%
“…Thus, the two eCBdegrading enzyme inhibitors demonstrated therapeutic efficacy and the potential to modulate microglial phenotype. Our recent report shows that WWL70 inhibits not only ABHD6 but also prostaglandin E synthesis in BV2 microglia (126); these results suggest that eCB-independent mechanisms might also contribute to the therapeutic effect of WWL70 in the TBI mouse model. Another study examined the effects of SMM-189, a CB2R inverse agonist, on microglial phenotype in a TBI mouse model.…”
Section: Microglial Polarization By Ecb In Tbi Modelsmentioning
confidence: 81%
“…It has been reported that activation of NF-κB is involved in the induction and maintenance of inflammatory pain, which can be weakened by the use of NF-κB inhibitors [ 33 , 34 ]. Our previous study also demonstrated that WWL70 inhibited NF-κB transcriptional activity in BV2 cells and attenuated NF-κB phosphorylation in the EAE mouse spinal cord [ 21 , 24 ]. To elucidate the potential mechanisms underlying the reduced pro-inflammatory cytokines in WWL70 treated CCI mice, we first examined NF-κB phosphorylation in the DRG and sciatic nerve.…”
Section: Resultsmentioning
confidence: 99%
“…The production and release of inflammatory mediators, such as interleukin-1β (IL-1β), IL-6, tumor necrosis factor alpha (TNF-α), and prostaglandin E 2 (PGE 2 ) from activated microglia, lead to activation of adjacent astrocytes [ 23 ], which then act in concert to excite nociceptive neurons causing persistent pain [ 3 ]. We recently reported that the ABHD6 inhibitor WWL70 suppressed PGE 2 production and the expression of its synthetic enzymes cyclooxygenase-2 (COX-2) and prostaglandin E synthase (PGES) in reactive microglia [ 24 ]. In agreement with these results, we find in this study that WWL70 significantly reduced neuropathic pain through interference with arachidonic acid (AA) metabolism and PGE 2 production rather than inhibition of 2-AG breakdown.…”
Section: Introductionmentioning
confidence: 99%